Análisis comparativo entre estructuras de hormigón armado y paneles de poli-estireno para el mercado de Calceta - Camana Moreira, Cristopher Andrés (2018)
The need to manage the comparative analysis between reinforced concrete structures and polystyrene panels for the market of the city of Calceta, through the use of viable structural alternatives for the reconstruction of the market of the city of Calceta, Cantón Bolívar, Province of Manabí, so that the set of studies and socioeconomic evaluations allow the decision to make or not an investment for the reconstruction of the market of the city of Calceta, destined to satisfy a certain collective need. The present work was modeled in the ETABS software, later two models were generated, corresponding to the studied systems, a reinforced concrete structures system and the other with the polystyrene panels system. These systems were included in the structural models in order to determine the contributions of these………